Wartość, wartościowanie i doświadczanie wartości w argumentacji prawniczej: [Value, valuation and experiencing value in legal argumentation] (Studia Prawnicze / The Legal Studies, 1985)
The author assumes that the problems of axiology, as well as all problems of practical philosophy, have to be treated in connection with the theory of actions and social relations. He accepts the institutional concept of axiology, i.e. according to him the existing social institutions are decisive as far as understanding of value is concerned, although not solely decisive. Values, valuation and axiological operations are subordinate to such subjects as the individual, collective body or other institutional persons. Thus, the existence of a category of value is a culturally conditioned fact.In the second part of the work the author presents legal problems of valuation. He considers the following issues: valuation on the basis of a norm, legal subsumption and valuation, formulation of legal frames, conflicts of values in notions, legal hermeneutics and valuation, binding force of law and valuation.